Projeto em Light Steel Frame : a modelagem e compatibilização em BIM - Ribeiro Junior, Edgard (2019)
The Light Steel Framing (LSF) consists of a metal structure made up of industrialized parts with millimeter adjustments, which require a more rational and descriptive design. Because of this, the use of BIM has been disseminated as a new tool, changing the way of thinking and elaborating the project, starting from a virtual construction of the building before a physical construction, in a fast and sustainable way. The idea is to solve the problems in construction site with parametric software, which aim at an improvement of the construction process, avoiding errors in the execution process, quantification, cost, coordination and maintenance. This dissertation aims to identify the transformations of the design process in BIM from a prototype of housing in LSF developed in Computer Aided Design (CAD). In this context the work allows to evaluate the impact of the transformation of a CAD project to be converted into BIM; define the BIM modeling processes from Level of development (LODs); besides performing a three-dimensional compatibilization between the architectural projects and the structure in LSF together with its electrical, hydraulic and exhaust subsystems; to produce three-dimensional models and the generation of conflict reports to identify the main conflicting project disciplines, as well as to highlight those that require greater attention from the BIM coordinator. As a methodological process, it was based on the analysis of the process map of the workflow of the CAD platform in relation to BIM, verifying its divergences in the application of the process through a diagnosis. This application was made from the Revit modeling processes of the architectural and complementary projects to use the Navisworks interference verification tool. The verification was carried out using the prototype in LSF, of UFMT in housing of social interest (HIS) developed by Duarte (2017). As a result it was possible to observe that during the application of the CAD versus BIM process map, it was observed that the CAD follows a production sequence in a linear way, already in BIM this workflow occurs simultaneously between all the design disciplines , with the gain of greater productivity in the integration of the disciplines and indicating a shorter elaboration time. In the case of LODs, the structural elements of LSF were related to modeling in different LODs. It is noticed that the greater the level of detail in LOD, the greater the degree of reliability and accuracy of the files and information to be extracted. In the compatibilisations, project interferences were added that allowed to establish a checklist to orient in the process of compatibilization of new projects in LSF. It was also possible to rank relationships between disciplines with the greatest potential for conflict.